(untitled) (Bangladesh Journal of Medical Science, 2020)
Objective: Scientific research provide information concerning an insufficient level of physical activity of young people. This study was conducted to determine the levels of physical activity among university students. Materials and Methods: In 2014-2015 academic year, 510 students voluntarily participated in this study. To obtain data, the Personal Information Form and to determine the levels of physical activity. International Physical Activity Questionnaire (IPAQ) were used. Results and Discussion: It is found that the 32.8% of students were not physically active, 49.2% of them had low physical activity level, 18% of students had adequate physical activity level to protect their health. Although it was found that the male students’ physical activity scores, moderately intense activity scores, intense activity scores and walking activity scores significantly higher than girls’ activity scores (p<0.05), there is no significant difference between sitting activity scores (p<0.05). Between students who have Body Mass Index over and under 25 kg/m2, there was no significant difference found between total physical activity, moderately intense activity, intense activity, walking activity and sitting time scores (p<0.05). Conclusion: It was determined that university students have low levels of physical activity and male students have higher physical activity levels than female students. Bangladesh Journal of Medical Science Vol.19(4) 2020 p.625-631